Growth and mineral contents of aromatic vegetable soybean (Glycine max) genotypes in acidic soil and its potential in combating the malnutrition - PAN, R S; NAIK, S K; SHINDE, RESHMA; DAS, BIKASH; KUMARI, MEENU; KUMAR, RAKESH; SINGH, A K; DAS, ANUP (The Indian Journal of Agricultural Sciences, 2025)
Vegetable soybean (Glycine max L.) stands out as a nutritious source, capable of fulfilling a substantial portion of daily nutritional requirements (RDA) for individuals, particularly those with limited resources. A field experiment was conducted during 2019 to 2021 at ICAR Research Complex for Eastern Region, Farming System Research Centre for Hill and Plateau Region, Ranchi, Jharkhand to evaluate the nutritional potential of seven aromatic vegetable soybean genotypes (AGS-447, AGS-456, AGS-457, AGS-458, AGS-459, AGS-460 and AGS-461) and one non-aromatic variety Swarna Vasundhara in acidic soils of Jharkhand. Results showed that AGS-458 emerged as the most promising in protein (11.28 g/100 kg FW), phosphorus (230 mg/100 kg FW), potassium (680 mg/100 kg FW), sulphur (92.3 mg/100 kg FW), iron (5.22 mg/100 kg FW) and zinc (1.71 mg/100 kg FW) content. Highest amount of Ca content (161 mg/100 gm FW) was found in genotype AGS-461, while AGS-459 had highest amount of Mg content (118 mg/100 FW). Among genotypes, average nutritional value was ~9.81 g protein, 199 mg P, 609 mg K, 107.4 Ca, 84.6 mg, 81 mg S, 4.5 mg Fe and 1.57 mg Zn/100 g of fresh edible portion (shelled green beans). Thus, vegetable soybean can be successfully grown in nutrient deficient soil, offering a nutrient supplement potential of 13–30% RDA. Genotype AGS-458, which exhibited the highest minerals was best in Jharkhand for poor tribal community.